Volatile Compounds and Biological Activities of Extracts of Cananga Odorata and its Petal-Derived Callus - Zain, Nurazah (2009)
Ylang-ylang is a flower of Cananga odorata (family of Annonaceae) tree or locally known as "kenanga". The flowers produce pleasant, sweet-scented and high value essential (volatile) oil that is widely used as aromatherapy and in perfumery industries. The importance of volatile oil in C. odorata has led to the alternative production of volatile compounds through plant cell culture such as callus and cell suspension culture. In this study, optimization of pH of the culture medium, different light incubation, plant growth regulators and carbon sources were conducted to develop a suitable growth medium for C. odorata petal-derived callus induction. The essential oil from flower, leaf and petal-derived callus of C. odorata were extracted through hydro-distillation process using simultaneous distillation extraction (SDE) and analysis of the volatile compounds were performed by using gas chromatography equipped with flame ionization detector (GC-FID). On the other hand, the biological properties of C. odorata flower, leaf and petal-derived callus were evaluated by using antioxidant, antimicrobial and seed germination assays. Results showed that C. odorata callus was best induced from petals of the C. odorata flowers, which cultured on basal Murashige and Skoog (MS) medium, Gamborg (B5) vitamins containing 30 g/L sucrose and 3 g/L agar supplemented with 3 mg/L NAA plus 0.5 mg/L BAP which gave the highest growth (0.98 ± 0.00 g/culture FW) at pH 5.7, 25 ± 2 oC and in dark condition after 4 weeks of culture. The volatile compounds detected by GC-FID from C. odorata flower essential oils were such as limonene, linalool, benzyl acetate and β-caryophyllene. While, from the leaf essential oils were α-pinene and β -caryophyllene. However, none of the volatile compounds mentioned above was detected from C. odorata petal-derived callus. The essential oil obtained from C. odorata flower and leaf showed antioxidant activity, especially in inhibiting lipid peroxidation. Result from antibacterial assay showed that flower essential oil was able to inhibit the growth of bacterial strains tested. The flower and leaf essential oil of C. odorata also showed antifungal activity against fungal strains tested. In seed germination assay, the germination percentage of Brassica nigra seeds was reduced when exposed to C. odorata flower and leaf essential oils at concentration of more than 2 mg/ml. The biological properties of C. odorata essential oils were possibly due to the presence of volatile compounds such as linalool, eugenol and other volatile compounds that could cause synergistic effects.